Isolation and Genetic Analysis of Multidrug Resistant Bacteria from Diabetic Foot Ulcers - Shahi, Shailesh K.; Kumar, Ashok (Frontiers in Microbiology, 2016)
Severe diabetic foot ulcers (DFUs) patients visiting Sir Sunderlal Hospital, Banaras Hindu University, Varanasi, were selected for this study. Bacteria were isolated from swab and deep tissue of 42 patients, for examining their prevalence and antibiotic sensitivity. DFUs of majority of the patients were found infected with Enterococcus spp. (47.61%), Escherichia coli (35.71%), Staphylococcus spp. (33.33%), Alcaligenes spp. (30.95%), Pseudomonas spp. (30.95%) and Stenotrophomonas spp. (30.95%). Antibiotic susceptibility assay of 142 bacteria with 16 antibiotics belonging to eight classes showed the presence of 38 (26.76%) isolates with multidrug resistance (MDR) phenotypes. MDR character appeared to be governed by integrons as class 1 integrons were detected in 26 (68.42%) isolates. Altogether six different arrays of genes (aadA1, aadB, aadAV, dhfrV, dhfrXII and dhfrXVII) were found within class 1 integron. Gene cassette dhfrAXVII-aadAV (1.6 kb) was present in 12 (3 Gram positive and 9 Gram negative) isolates and was conserved across all the isolates as evident from RFLP analysis. In addition to the presence of class 1 integron, six β-lactamase resistance encoding genes namely blaTEM, blaSHV, blaOXA, blaCTX-M-gp1, blaCTX-M-gp2 and blaCTX-M-gp9 and two methicillin resistance genes namely mecA and femA and vancomycin resistance encoding genes (vanA and vanB) were identified in different isolates. Majority of the MDR isolates were positive for blaTEM (89.47%), blaOXA (52.63%) and blaCTX-M-gp1 (34.21%). To our knowledge, this is the first report of molecular characterization of antibiotic resistance in bacteria isolated from DFUs from North India. In conclusion, findings of this study suggest that class-1 integrons and β-lactamase genes contributed to the MDR in above bacteria.